Helicobacter pylori infection and growth delay in older children. Issue 1 (1st July 1997) - Perri, Francesco; Pastore, Maria; Leandro, Gioacchino; Clemente, Rocco; Ghoos, Yvo; Peeters, Marc; Annese, Vito; Quitadamo, Michele; Latiano, Anna; Rutgeerts, Paul; Andriulli, Angelo
Abstract : It is thought that Helicobacter pylori infection may influence growth rate in children. The aim of this study was to evaluate the prevalence of H pylori infection in healthy Italian children, and to look for differences in height between infected and non-infected subjects. Two hundred and sixteen children, aged 3 to 14 years, were tested for H pylori infection by 13 C-urea breath test. Centile values for height were calculated. Composite indices for socioeconomic class and household crowding were also determined. Forty nine of 216 children (22.7%) were H pylori positive. The prevalence of infection increased with age. Eight of 49 H pylori positive children (16.3%) were below the 25th centile for height, compared with 13 of 167 H pylori negative children (7.8%). This difference became significant in children aged 8.5 to 14 years; in this group (n = 127), eight of 31 infected children (25.8%) were below the 25th centile for height, compared with eight of 96 non-infected children (8.3%). A significant correlation was found between socioeconomic conditions, household crowding, and H pylori status. By using stepwise logistic regression, only the centile value for height was significantly related to H pylori status in older children. Thus H pylori infection was associated with growth delay in older children, poor socioeconomic conditions, and household overcrowding. This finding is consistent with the hypothesis that H pylori infection is one of the environmental factors capable of affecting growth.